On fluctuations in velocity fields during convective mass transfer in hydrogen generation through water electrolysis - Diehl de Oliveira, Jeferson; Cardoso, Elaine Maria [UNESP]; Rodrigues de Souza, Reinaldo; Copetti, Jacqueline Biancon; Varón, Lina Maria; Simões Moreira, José Roberto (Elsevier, 2024)
This study investigates the hydrodynamic behavior and mass transfer performance in water electrolysis within an alkaline solution (30% wt KOH). By using a glass electrolyzer with vertical stainless steel 304 electrodes spaced 20 mm apart, the research employs an optical flow method to analyze the velocity field of hydrogen bubbles. Image sequences captured by a CCD camera with a pixel resolution of 67.2 μm facilitate this analysis. The study focuses on the effect of current density, ranging from 33 to 650 A/m2. Experimental results demonstrate that the velocity distribution in most areas of the electrolyzer is primarily influenced by two asymmetric flow patterns caused by the buoyancy of hydrogen and oxygen bubble layers. Regions with lower depths exhibit increased velocity and vorticity fields, resulting in greater motion within the electrolyte. Conversely, at higher current densities, the average velocity decreases due to the expansion of dynamic areas. These complex flow structures significantly affect bubble dynamics, causing velocity fluctuations between the electrodes. The findings offer valuable insights into hydrogen bubbles' dynamics and transport phenomena within the electrolyzer, enhancing the understanding of bubble behavior in alkaline water electrolysis.
Keywords: Electrolysis; Hydrogen generation; Renewable energy; Velocity field